2014
DOI: 10.3748/wjg.v20.i15.4362
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of esomeprazole and lansoprazole in triple therapy for eradication ofHelicobacter pyloriin Japan

Abstract: Esomeprazole showed non-inferiority and safety in a 7 day-triple therapy for eradication of H. pylori compared with lansoprazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…13 However, we treated these PPIs with 30 mg bid (60 mg/d) dose of lansoprazole, 20 mg bid (40 mg/d) dose of esomeprazole, or 10 mg bid (20 mg/d) dose of rabeprazole in the same group, because previous RCTs showed no difference of eradication rate between lansoprazole 30 mg bid (60 mg/d) and rabeprazole 10 mg bid (20 mg/d), 14 in addition, between lansoprazole 30 mg bid (60 mg/d) and esomeprazole 20 mg bid (40 mg/d). 15 This treatment of PPIs also supported by our previous data. 16 We need to emphasize the standard dose of PPIs in this study, because previous meta-analysis concluded high-dose PPI seems more effective than standard dose for curing H. pylori infection in 7-day triple therapy.…”
Section: Treatmentsupporting
confidence: 83%
“…13 However, we treated these PPIs with 30 mg bid (60 mg/d) dose of lansoprazole, 20 mg bid (40 mg/d) dose of esomeprazole, or 10 mg bid (20 mg/d) dose of rabeprazole in the same group, because previous RCTs showed no difference of eradication rate between lansoprazole 30 mg bid (60 mg/d) and rabeprazole 10 mg bid (20 mg/d), 14 in addition, between lansoprazole 30 mg bid (60 mg/d) and esomeprazole 20 mg bid (40 mg/d). 15 This treatment of PPIs also supported by our previous data. 16 We need to emphasize the standard dose of PPIs in this study, because previous meta-analysis concluded high-dose PPI seems more effective than standard dose for curing H. pylori infection in 7-day triple therapy.…”
Section: Treatmentsupporting
confidence: 83%
“…Lansoprazole, ESO, and RPZ have different effects on intragastric pH . Here, we used 30‐mg bid (60‐mg/day) LPZ, 20‐mg bid (40‐mg/day) ESO, or 10‐mg bid (20‐mg/day) RPZ because a meta‐analysis and two RCTs showed no difference in eradication rates between these standard doses of PPIs, although a high dose of PPIs is more effective . These data indicate importance of acid suppressant in eradication.…”
Section: Methodsmentioning
confidence: 99%
“…18 To confirm successful eradication, we performed UBTs using UBIT 100 mg tablets (Otsuka Pharmaceutical) at least 4 weeks after the drug regimens concluded (typically around 8 weeks). All subjects were instructed not to take PPIs or VPZ from the time 22 Here, we used 30-mg bid (60-mg/day) LPZ, 20-mg bid (40-mg/day) ESO, or 10-mg bid (20-mg/day) RPZ because a meta-analysis 23 and two RCTs 24,25 showed no difference in eradication rates between these standard doses of PPIs, although a high dose of PPIs is more effective. 23 These data indicate importance of acid suppressant in eradication.…”
Section: Methodsmentioning
confidence: 99%
“…The eradication rate using traditional first-line therapy is low (70%) due to the increase in CLR resistance 11,17,18. 14 The Japanese government insurance has allowed first-line (PPI-AMX-CLR) and second-line (PPI-AMX-MTZ) eradication therapy.…”
mentioning
confidence: 99%